Factors influencing adoption of vertical forced-air sulfur dioxide fumigation technology of fresh longan exporters in Thailand - Sevilai, Rasiga; Varith, Jaturapatr; Kanchanawong, Paisarn; Pimpimol, Jakrapong; Aroonsrimorakot, Sayam (Interdisciplinary Research Review, 2020)
The research aimed to study the factors influencing an adoption of vertical forced-air SO2 fumigation technology of longan exporters of Thailand. A questionnaire was applied as a tool of data collection, from 101 representative samples in the northern and eastern regions of Thailand which are two main plantation areas of fresh longan. Statistical analysis was applied by factor analysis from the in-depth interviews with 36 variables. The result indicates that there were 28 factors in 6 components which influenced the exporters’ decision in adopting the technology with the sum of variance of 53.958%. These components were worthiness, competitiveness, organization goals, operations, management, and technological hindrance. Our findings are useful for further development of the strategic plan and policy, especially for the fresh longan exporters of Thailand, to enhance an adoption of SO2 fumigation with vertical forced-air technology for safer operation and better food safety.